Heme on Pulmonary Malaria: Friend or Foe? - Pádua, Tatiana Almeida; Souza, Mariana Conceição (Frontiers in Immunology, 2020)
Malaria is a hemolytic disease that, in severe cases, can compromise multiple organs. Pulmonary distress is a common symptom observed in severe malaria caused by Plasmodium vivax or P. falciparum. However, biological components involved in the development of lung malaria are poorly studied. In experimental models of pulmonary malaria it was observed that parasitized red blood cell-congested pulmonary capillaries are related to intra-alveolar hemorrhages and inflammatory cell infiltration. Thus, it is very likely that hemolysis participates in malaria-induced acute lung injury. During malaria, heme assumes different biochemical structures such as hemin and hemozoin (bio-crystallized structure of heme inside Plasmodium sp.). Each heme-derived structure triggers a different biological effect: in one hand hemozoin found in lung tissue is responsible for the infiltration of inflammatory cells and consequent tissue injury, whereas on the other hand heme stimulates HO-1 expression and CO production, which protect mice from severe malaria. In this review, we discuss the biological mechanism involved in the dual role of heme response in experimental malaria-induced acute lung injury.